Development of Noise Database for Noise Impact Assessment Expert System - Lakai, Cecelia (1998)
The Noise Assessment Database Expert System (NADES) was designed to identify the characteristic of changes in the existing noise environment as a result of the a proposed development, noise effects and proposed mitigating measures to reduce these impacts. The NADES was developed using the C Language Integrated Production System (CLIPS) version 6.04, an Expert System Shell which is designed by NASA (National Aeronautics and Space Administration). The development of NADES was based on Environmental Impact Assessment (EIA) reports submitted to Department of Environment (DOE) and also on three assumptions: all reports are subjected to the Environmental Quality (Prescribed Activities) (Environmental Impact Assessment) Order 1978, project activities are as listed under the Checklist of Project Activities for Prescribed Activities and all EIA reports reviewed were approved by DOE. The NADES have the basic components of a typical expert system and it was developed to produce an EIA report in a much shorter time.